TYPES OF VOCABULARY (World Bulletin of Social Sciences, 2022)
The theory and practice of compiling dictionaries in the article, the fact that the original dictionaries were systematic in their knowledge of the language, was created even before it became a linguistics, the task of the lexicographer, "correct" to all common words it is given that there is a need to correct the language by giving meaning, spelling, and stress, and to add these words to the dictionary, for all useful things should be accepted